Recognizing and Transforming Madness, Citizenship, and Social Justice: Toward the Revolution in Risk Management and the Overcoming of Captivity: A Response to Brown and Ward. (June 2013) - Arrigo, Bruce A.
Psychological Jurisprudence (PJ) is a philosophy about the self in society and it is a cultural critique of captivity and risk management. This article further clarifies or amplifies several of PJ's central arguments relative to its rediagnosis of madness, deconstruction of citizenship, and reconstitution of social justice. These concerns draw attention to the theory, method, and praxis of PJ, including their relevancies for institutional and community-based reform within the mental health and criminal justice systems. These matters are provisionally addressed, mindful of the respective comments developed by Professors Brown and Ward.